The Marketing Strategy for Small-Scale Garment Products on Post-Pandemic Era - ., Muhardi; Oktini, Dede R.; ., Nurdin; Hami, Norsiah; Omar, Salmah; Shafie, Shafini Mohd (KnE Social Sciences, 2023)
The small-scale garment industry has gained significant influence in Indonesia. However, with the challenges posed by the pandemic era, the industry must adapt to ensure its long-term sustainability. The objective of this research is to analyze the marketing strategy of small-scale garment products, specifically examining the proportion of online and offline marketing strategies, as the success of these products in the market relies on the effective utilization of both strategies. The urgency of this research stems from the daily market demand for garment products and the crucial role played by dominating small-scale garment companies in contributing to the economy’s development. This research adopts a mixed-method approach, incorporating both qualitative and quantitative methods. The qualitative approach involves conducting interviews with owners of small-scale garment businesses, commonly known as convection businesses. Meanwhile, the quantitative approach is used to analyze the proportion of online and offline marketing strategies. The qualitative analysis utilizes a Markov approach to provide insights into future marketing strategy proportions and possibilities. The research was conducted at a small-scale garment center located in Kutawaringin Village, West Bandung Regency. The results indicate that during the pandemic era, garment businesses have increasingly embraced online marketing strategies to enhance their marketing performance. Furthermore, businesses that have traditionally relied on offline marketing are also increasing their proportion of online marketing strategy implementation. Keywords: marketing strategy, small-scale garment business, online, offline